Student’s creative thinking ability in problem-posing activities viewed from self-efficacy - Husna, Insana Akmalul; Kurniasih, Ary Woro (Unnes Journal of Mathematics Education, 2019)
This study aims to determine the completeness of students' creative thinking abilities in knowing students' creative thinking processes in terms of self-efficacy, knowing students' responses to creative problem-solving learning with problem-posing activities, and knowing the obstacles experienced in learning. This research is a mixed-method with councurrent-embedded strategy. The sample of this study was one of class VIII in a Junior High School in Blora. The results showed that: (1) students' creative thinking skills with creative problem solving learning achieve mastery learning; (2) the description of the stages of students' creative thinking in terms of the level of self-efficacy that is on subjects who are in level of creative thinking ability 1 at the level of low and moderate self-efficacy is only able to pass the stage of synthesizing ideas and building ideas. Subjects at the level of creative thinking ability 2 at moderate and low levels of self-efficacy synthesize ideas and build ideas. Subjects at level of creative thinking ability 3 at moderate and high levels of self-efficacy are able to go through all stages of creative thinking, namely synthesizing ideas, building ideas, planning the application of ideas and applying ideas; (3) The use of creative problem solving learning models in which there are problem-posing activities get positive responses from students; (4) The obstacle experienced in this study is that this study when learning is used too much for group discussions.